A consistência no pareamento homotípico por tamanho ao longo e entre estações reprodutivas não depende da variação de tamanho na aranha basílica Mecynogea lemniscata (Araneidae) - Castro, Vítor Campos de (2024)
Identifying assortative mating patterns is crucial for understanding genetic changes. However, to accurately estimate assortative mating in a population, it should be measured within and between breeding seasons, because the consistency of size- assortative mating across different temporal scales is often low in animals. In addition, describing size variation of males and females between temporal scales is important to avoid Simpson’s paradox. We assessed sexual size dimorphism, the effects of ontogeny, size differences within each sex, and the consistency of size-assortative mating within and between breeding seasons in the basilica spider, Mecynogea lemniscata. We collected mating pairs of M. lemniscata in a eucalyptus plantation, located in the Brazilian savanna, across two breeding seasons (2022 and 2023/24) and in four periods of the 2023/24 breeding season. We measured body mass and carapace width of spiders. Males matured earlier than females and guarded subadult partners. Although adults were larger and heavier than subadults, ontogeny did not affect assortative mating patterns. Females were generally heavier than males in the 2023/24 breeding season but not in 2022; however, these changes did not influence mate assortments, as pairings were random based on body mass in both seasons. Despite varying size differences between seasons, size-assortative mating remained homotypic based on carapace width across seasons and within the 2023/24 season. Homotypic size-assortative mating was consistent across different temporal scales. Unlike other species, temporal size variation in M. lemniscata spiders did not disrupt assortative mating patterns. We urge other researchers to investigate temporal variation in body size and assortative mating, thereby examining the underlying mechanisms that maintain a consistency in size-assortative mating.